Traumatic Thoracic Aorta Injuries: Outcomes up to 15 years Post Thoracic Endovascular Aortic Repair - Sharma, Varun J; Jarmin, Martin J; Crozier, John A; Gupta , Saksham; Iliopoulos, Jim N (Journal of Endovascular Resuscitation and Trauma Management, 2020)
Background: Aortic injuries are a leading cause of death following trauma, with 75% pre- and 50% in-hospital mortality. Endovascular repair is technically easier with fewer complications but long-term results are unproven. Methods: A retrospective analysis of patients with endovascular repair of thoracic aortic injuries from 2001 to 2018 at Liverpool Hospital, Sydney, Australia was undertaken. Primary endpoint was death and secondary endpoints were re-interventions, hand ischemia, access vessel repair and ischemic complications. Results: 24 patients (10 female) were reviewed, the most common mechanism of injury being motor-vehicle related (75%) in Zone 3 (71%). Deployment was proximal (n = 11), on (n = 2) or distal (n = 11) to the left subclavian artery (LSCA). Average follow-up was 5.4 ± 5.1 years (range 0.1–15.2 years), with two deaths. At <90 days, complications were hand ischemia (n = 4, n = 1 needing intervention), access vessel endarterectomy (n = 1) and conversion to open bypass (n = 1). At >90 days, complications were hand ischemia (n = 1), graft migration (n = 2) and minor graft thrombosis (n = 1). Coverage of LSCA was not a predictor of re-intervention (P = 0.43) or supra-aortic bypass (P = 0.13). Survival free from reintervention in the non-covered LSCA group was 100% at the 30-day and 6-month timepoints, and 80% at the 1-year and 5-year timepoints. Survival free from reintervention in the covered LSCA group was 84%, 75.6%, 67.2% and 67.2% at the 30-day, 6-month, 1-year and 5-year timepoints, respectively. Conclusions: Endovascular repair for aortic injuries has low levels of morbidity. The LSCA can be covered without arm ischemia and is not predictive of re-intervention or a supra-aortic bypass. At up to 15 years follow-up, graft complications remain low.